Case Study On The Effect Of Audiovisual Media On The Concentration Of Children With Adhd (Attention Deficit Hyperactivity Disorder) - Tia Septiani; Brigita Puridawaty; Nuni Puji Rahayu; R. Dewi Dharina; Heni Srigunawati; Eva Nurchafiah (Kirana Publisher (KNPub), 2026)
Children with Attention Deficit Hyperactivity Disorder (ADHD) experience major difficulties in attention control, impulse regulation, and behavioral self-regulation, which affect their engagement in classroom learning. This study aims to describe the effect of audio-visual media on improving learning concentration in an early childhood student with ADHD tendencies. The research employed a qualitative descriptive approach using a case study method involving a five-year-old boy enrolled in an Islamic kindergarten. Data were collected through participant observation, interviews with teachers and parents, and supporting documentation, including developmental records and psychological assessment results. The findings indicate that prior to the intervention, the child showed limited attention span, high distractibility, and difficulty following learning instructions. After the implementation of structured learning activities supported by audio-visual media, improvements were observed in attention duration, active engagement in learning activities, and the ability to follow simple instructions. Audio-visual media were effective in directing the child’s attention through the integration of visual and auditory stimuli, thereby reducing environmental distractions. This study concludes that audio-visual media have the potential to serve as an effective pedagogical strategy to support learning concentration in children with ADHD when applied consistently and developmentally appropriately in early childhood education settings.